Avaliação das propriedades físico-químicas e osteogênicas do cimento portland associado ao pentóxido de nióbio - Silva, Rafaela Alcindo (2022)
Work aimed to develop, characterize and evaluate the osteogenic activity of PC formulations with different proportions of Niobium oxide (Nb2O5), replacing Bi2O3. Three groups were used, one control and two experimental: GC (MTA Angelus®), F6 (75% CP, 20% Nb2O5 and 5% CaSO4) and F7 (75% CP, 10% Bi2O3, 10% Nb2O5e 5% CaSO4) . The formulations were submitted to X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), X-ray Fluorescence Spectrometry (FRX), pH, setting, radiopacity, compressive strength, cytotoxicity and bioactivity. The data obtained were statistically evaluated by the test of variance (ANOVA) with Bonferroni correction (p<0.05%). The pH test result: Niobium 10% Immediate (12.205 ±0.304); 24h; (12.770 ± 0.226) 48h: (12.910 ± 0.169). Niobium 20%: immediate (12.080 ± 0.282); 24h: (12.350 ± 0.593); 48 h: (12.580 ± 0.73). For initial setting time in seconds: MTA (397,500 ±10,606); Niobium 10% (294,333 + 90,897) and Niobium 20% (279,000 + 15,874). The final setting time for the groups were: MTA (15,000 + 49,497), Niobium 10% (560 ± 38,587), being smaller when compared to MTA (p<0,001) and Niobium 20% (715,666 ± 30,664) (p<0 .01). Radiopacity values in mm Al of 10% Niobium (3.888 ±0.340); Niobium 20% (3.713 ± 0.712). The compressive strength in MPa was: Niobium 10% (694.150 + 78.951) Niobium 20% (699.295 + 47.672). Cell viability showed no difference between MTA and experimental groups (p<0.05). The results of the osteogenesis capacity of the formulations from the alkaline phosphatase assay (ALF) in IU/L per gram of protein for each group were: MTA (1.9 + 1.227) and Niobium 20% (1.784 + 1.342) (p> 0.05). Our findings point to relevant properties for Nb2O5 formulations such as alkaline pH, radiopacity, compressive strength and alkaline phosphatase activity.